Current status of Philippine mollusk museum collections and research, and their implications on biodiversity science and conservation - Ramos, Dino Angelo E.; Batomalaque, Gizelle A.; Anticamara, Jonathan A. (2018)
Mollusks are an invaluable resource in the Philippines, but recent reviews on the status of museum collections of mollusks or research trends in the country are lacking. Such assessments can contribute to a more comprehensive evaluation of natural history museums in the Philippines, as well as biodiversity management. This review showed that local museums in the Philippines have much to improve in terms of their accessibility and geographic coverage in order to effectively cater to research and conservation needs of the country. Online access to databases was lacking for local museums, making it cumbersome to retrieve collection information. The UST museum held the most species and subspecies across all museums (4899), comparable to the national museums of countries such as the USA and France. In terms of size, there were larger Philippine mollusk collections in museums abroad. Majority of mollusk specimens come from Regions 4 and 7, while the CAR and Region 12 were least sampled. Publications on Philippine mollusks are dominated by taxonomic and biodiversity research. Around 80% of publications were on marine species. Therefore, there is a great need to (1) improve access to collections by publishing databases and collections online; (2) improve spatial coverage of mollusk sampling to have a better nationwide (and habitat) representation of Philippine mollusk diversity; (3) fill important knowledge gaps in the ecological assessment of exploited mollusks and minor taxa that will be useful in status assessment and management; and (4) build a network of functional museums to facilitate mollusk and invertebrate researches and conservation by making properly curated specimens available to more researchers nationwide.